Photodynamic therapy versus systemic antibiotic for the treatment of periodontitis in a rat model. Issue 7 (4th February 2019) - Zhang, Jianxing; Liang, Hui; Zheng, Yixin; Wang, Dongcai; Xia, Jiang; Peng, Wenming; Cheng, Kangjie; Wang, Lianfei; Liu, Yunfeng; Peng, Wei; Li, Qingyong
Abstract: Background: To compare the therapeutic effect of photodynamic therapy (PDT) with Toluidine blue O hydrogel versus systemic antibiotic (SA) in treating periodontitis on rats. Methods: Thirty‐two Wistar rats were divided into four groups and treated differently: Negative control (NC) group, normal rats; positive control (PC) group, rats with periodontitis; SA group, rats with periodontitis treated with systemic antibiotic; PDT group, rats with periodontitis treated with PDT. After treatment, gingival sulcus bacterial load was measured by counting the colony forming units per milliliter (CFU mL −1 ). The tooth and periodontal tissues were histologically processed to analyze histological and immunohistochemical profile. Gingival samples were obtained to quantify interleukin‐1 beta (IL‐1β) and tumor necrosis factor‐alpha (TNF‐α) levels. Results: Gingival sulcus bacteria load is significantly lower in PDT group compared with the SA group. The histological analysis showed that some extremely effective repair signs of periodontal tissue were presented in PDT group, such as no periodontal pocket, no bone resorption, few inflammatory cells, massive fibroblasts and collagen fibers. Several effective repair signs of periodontal tissue were also observed in SA group, such as shallow periodontal pocket, small amount of inflammatory cells, substantial fibroblasts and collagen fibers. There were lower cyclooxygenase‐2, matrix metalloproteinase ‐8 (MMP‐8) and RANK immunolabeling, higher osteoprotegerin immunolabeling in PDT group compared with SA group. The IL‐1β and TNF‐α levels in PDT group were lower than those in NC group, but higher than those in SA group. Conclusion: PDT was effective to treat experimental periodontitis and was superior to systemic metronidazole as a treatment for periodontitis.